Occurrence of Escherichia coli carrying Shiga toxin-producing genes in buffaloes on smallholdings in Bangladesh - Mukta Das Gupta; Arup Sen; Ashutosh Das (Veterinary World, 2018)
Background and Aim: Shiga toxin-producing Escherichia coli (STEC) has emerged as significant foodborne pathogens. Ruminants are the primary reservoir of the zoonotic STEC. In Bangladesh, previous studies reported the presence of STEC in cattle, goat, and sheep; however, there is little information about STEC carriage by buffaloes. This study aimed to determine the occurrence of STEC in healthy (absence of clinical signs and symptoms) buffaloes on smallholdings in Bangladesh and to assess the antimicrobial resistance pattern of identified STEC isolates.